Analysis of the Relationship Between Motivation and Learning Outcomes of Chinese Language Education Students Class of 2022 Semarang State University in the Chuji Hanyu Xiezuo Xia Course - Listianto, Ridwan; Siregar, Sheyra Silvia; Marsuki, Ria Riski (Universitas Negeri Semarang, 2025)
This study aims to analyse the relationship between motivation and learning outcomes of Chinese language education students in the 2022 batch of Semarang State University in the Chuji Hanyu Xiezuo Xia course